2005
DOI: 10.1111/j.1747-7379.2005.tb00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Selective Migration Matter? Explaining Ethnic Disparities in Educational Attainment among Immigrants' Children

Abstract: Understanding why some national‐origin groups excel in school while others do not is an enduring sociological puzzle. This paper examines whether the degree of immigrants’educational selectivity ‐ that is, how immigrants differ educationally from non‐migrants in the home country ‐ influences educational outcomes among groups of immigrants’children. This study uses published international data and U. S. Census and Current Population Survey data on 32 immigrant groups to show that as immigrants’educational selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(209 citation statements)
references
References 36 publications
(15 reference statements)
12
181
0
6
Order By: Relevance
“…Moreover, the mothers' level of education, usually considered as an indicator of the social status of origin, was significantly associated with mood and psychological well-being. This result does support previous literature (Feliciano, 2005;Sabatier, 2008). More specifically, the educational level of the parents and family wealth (material factors such as computers, leisure, books, etc.)…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Moreover, the mothers' level of education, usually considered as an indicator of the social status of origin, was significantly associated with mood and psychological well-being. This result does support previous literature (Feliciano, 2005;Sabatier, 2008). More specifically, the educational level of the parents and family wealth (material factors such as computers, leisure, books, etc.)…”
Section: Discussionsupporting
confidence: 77%
“…However, in our study with immigrant youth, no significant differences were found regarding the perception of health and well-being, except in what concerns Physical Well--being, which was reported significantly higher in boys. This finding is particularly important if we consider that, according to Neto (2001;2005), the adolescent's gender seems to be a predictor of life satisfaction and psychological adjustment in young immigrants. Moreover, the mothers' level of education, usually considered as an indicator of the social status of origin, was significantly associated with mood and psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though ethnically heterogeneous groups, for this study"s purposes, the aggregation of blacks and Hispanics is substantively supported by other studies finding black and Hispanic first and second generation immigrants to be a less-positively selected group than first and second generation Asian immigrants (C. Feliciano, 2005b;C. Feliciano, 2005c).…”
Section: Analytic Strategysupporting
confidence: 50%
“…Following the studies of Feliciano (2005bFeliciano ( , 2006 and Ichou (2014), this part of the analysis seeks to explain differences within the population children of immigrants, rather than vis-à-vis the majority (cf. Harris, Jamison, and Trujillo 2008;Levels, Dronkers, and Kraaykamp 2008).…”
Section: Resultsmentioning
confidence: 99%